COMPARISON OF GLUCOSE REDUCTION IN URINE USING BENEDICT METHOD HEATED BY METHYLATED FLAME WITH 100°C WATERBATH - Fitri Fadhilah; Noviana Vanawati (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2019)
The high prevalence of Diabetes Melitus (DM) is a global problem that must be solved by health workers around the world. This study aims to determine the differences in the results of urine reduction examination using benedict method heated by spirtus flame and waterbath 100°C. This research method is a laboratory experiment. The results of this study indicated that the urine reduction examination by heating methylated flame and waterbath 100oC shows the same results from negative (-) until positive (+4). Examination of urine reduction by heating the methylated flame and waterbath 100oC did not affect the results. However, there are a difference in the process of urine reduction examination by heating flame which was need a longer time up to 3-5 minutes. Additionally, the solution in the tube could be exploded. It was also time consuming which could only carry out one by one sample. Meanwhile, the heating of urine by using 100oC waterbath is relatively faster, which only took 2 minutes. The urine was not also exploded when it was boiled and the heating process could perform 6-8 samples at the same time (depending on the tube rack). In conclusion, the heating method of urine by using waterbath was better than spirtus (methanol) flame since it could carry out large sample in one time and it was safer for the laboratory personnel.